Glomalin and Contribution of Glomalin to Carbon Sequestration in Soil: A Review - MD. Belal Hossain (Turkish Journal of Agriculture: Food Science and Technology)
Arbuscular mycorrhizal fungi (AMF) improves the uptake of nutrients and water to the plants through mutual symbiosis. Only AMF produces glomalin related soil protein (GRSP). Acaulospora morroaiae, Glomus luteum, Glomus verruculosum, Glomus versiforme are the effective glomalin producing AMFs. Mixed primary forest, tropical rainforest, soil organic matter, clay soil, no tillage, quality and quantity of fertilizers, crop rotation, and water stable aggregates are also suitable to increase glomalin production. Glomalin is a glycoprotein that contains 30–40% carbon (C) which is assumed to be stable and persistent in soil. The glomalin can sequestrate more carbon in the soil due to its high carbon and aggregate stability. Greater aggregate stability leads to high organic carbon protection in terrestrial ecosystems. The lowest glomalin content (0.007 mg per gram soil) was found in Antarctic region, and the highest glomalin content (13.50 mg per gram soil) was observed in tropical rainforest. In agricultural soil, glomalin content varies between 0.30 and 0.70 mg per gram soil. The GRSP containing soil organic carbon (SOC) in deeper soil layers was 1.34 to 1.50 times higher than in surface layers. Glomalin can sequestrate 0.24 Mg C ha-1 in soil when present at 1.10±0.04 mg g-1. At elevated CO2 (700 µmol mol-1) level, easily extractable glomalin (EEG) and total glomalin (TG) were 2.76 and 5.67% SOC in the surface soil layer over ambient carbon dioxide (CO2) level. This finding indicates the effective function of GRSP C sequestration in soil under global environmental change scenarios. Glomalin can also protect labile carbon that can help regulating nutrient supply to the plants. No tillage practice causes higher AMF hyphal length, GRSP and water stable aggregate (WSA) compared to that of conventional tillage practice. The current review demonstrated that GRSP is an important tool for carbon storage in deep soils. Glomalin mediates soil aggregates, improves soil quality, increases carbon sequestration and crop production, and mitigates climate change.